Using SEM-EDX and ICP-OES to Investigate the Elemental Composition of Green Macroalga Vaucheria sessilis - Izabela Michalak; Krzysztof Marycz; Katarzyna Basińska; Katarzyna Chojnacka (The Scientific World Journal)
The biomass of Vaucheria sessilis forms algal mats in many freshwaters. There is a need to find the method of algal biomass utilization. Vaucheria sessilis is a rich source of micro- and macronutrients and can be used as a soil amendment. In the paper, the elemental composition of enriched, via bioaccumulation process, macroalga was investigated. For this purpose, two independent techniques were used: scanning electron microscopy with an energy dispersive X-ray analytical system (SEMEDX) and inductively coupled plasma optical emission spectroscopy (ICP-OES). The biomass was exposed to two microelemental solutions, with Cu(II) and Zn(II) ions. After two weeks of the experiment, macroalga accumulated 98.5 mg of Zn(II) ions in 1 g of dry biomass and 68.9 mg g−1 of Cu(II) ions. Micrographs performed by SEM proved that bioaccumulation occurred. Metal ions were bound on the surface and in the interior of cells. Mappings of all cations showed that in the case of the surface of biomass (biosorption), the elements constituted aggregations and in the case of the cross section (bioaccumulation) they were evenly distributed. The algal biomass with permanently bound microelements can find an application in many branches of the industry (feed, natural fertilizers, etc.).